Pengendalian Kualitas Kemasan Produk Biskuit di Industri Manufaktur dengan Metode DMAI - Ahmad Rizal Maulana; Siti Muhimatul Khoiroh (LPPM Universitas Pahlawan Tuanku Tambusai, 2026)
PT. XYZ, a biscuit manufacturing industry, faces a product quality decline issue due to a high rate of packaging defects. This study aims to identify the causes of these defects and formulate improvement strategies using the DMAI (Define, Measure, Analyze, Improve) method. Data collection focused on packaging defects analyzed using Pareto diagrams, p-control charts, and DPMO calculations. Root causes were identified using a fishbone diagram, and improvement proposals were structured through the 5W1H approach. The results revealed four main defects: leaking (28.21%), unsealed (26.47%), torn (23.16%), and faint coding (22.16%), with a DPMO level of 29.91. The main causes of defects were machine factors and a lack of operator accuracy. The proposed recommendations include implementing Standard Operating Procedures (SOP), preventive machine maintenance schedules, and regular operator training.